2019
DOI: 10.1097/md.0000000000014302
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis reveals driver long non-coding RNAs in osteosarcoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This present study demonstrated the prognostic significance of ASMTL-AS1 in patients with EOC. Previous studies also revealed that dysregulation of ASMTL-AS1 would be a useful biomarker of osteosarcoma and bladder cancer 27 28 . Here, we observed a falling expression level of ASMTL-AS1 in EOC different stages, from stage I/II to III/IV.…”
Section: Discussionmentioning
confidence: 97%
“…This present study demonstrated the prognostic significance of ASMTL-AS1 in patients with EOC. Previous studies also revealed that dysregulation of ASMTL-AS1 would be a useful biomarker of osteosarcoma and bladder cancer 27 28 . Here, we observed a falling expression level of ASMTL-AS1 in EOC different stages, from stage I/II to III/IV.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, ASMTL-AS1 was significantly decreased in gastric tissues and cells when compared with the normal ones. Due to the role of ASMTL-AS1 in mediating cell functions and predicting overall survival [ 14 , 15 , 26 ], we also hypothesized that this lncRNA may play a role as a tumor suppressor in gastric cancer and may have the potential as a prognostic marker. Therefore, the distinguishing ability of ASMTL-AS1 between survivors and non-survivors of patients also was analyzed by ROC curves, and the cutoff value was thus determined.…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of lncRNAs and their function in tumorigenesis is well investigated in osteosarcoma ( Table 1 ). A recent transcriptome profiling study based on the TARGET data detected a total of 13,903 expressed lncRNAs and their integrative gene expressions and SCNA analysis revealed 167 novel driver lncRNAs (including 2 previously reported lncRNA PVT1 and ZFAS1) to be associated with osteosarcoma ( Luo et al, 2019 ). Another microarray analysis noted 25,733 expressed lncRNAs in human osteosarcoma, among which 403 were upregulated and 798 were downregulated when comparing osteosarcoma tissues to adjacent normal tissues ( Li et al, 2018 ).…”
Section: Long Non-coding Rnasmentioning
confidence: 99%